Experimental analysis and theoretical predictions of the limit strains of a hot-dip galvanized interstitial-free steel sheet - Freitas,Maria Carolina dos Santos (2013)
In this work, the formability of a hot-dip galvanized interstitial-free (IF) steel sheet was evaluated by means of uniaxial tensile and Forming Limit Curve (FLC) tests. The FLC was defined using the flat-bottomed Marciniak's punch technique, where the strain analysis was made using a digital image correlation software. A plastic localization model was also proposed wherein the governing equations are solved with the help of the Newton's method. The investigated hot-dip galvanized IF steel sheet presented a very good formability level in the deep-drawing range consistent with the measured Lankford values. The predicted limit strains were found to be in good agreement with the experimental data of the hot-dip galvanized IF steel sheet owing to the definition of the localization model geometrical imperfection as a function of the experimental surface roughness evolution and, in particular, to the yield surface flattening near to the plane-strain stress state authorized by the adopted yield criterion.